2014
DOI: 10.1016/j.physletb.2014.08.018
|View full text |Cite
|
Sign up to set email alerts
|

The entropy of the noncommutative acoustic black hole based on generalized uncertainty principle

Abstract: In this paper we investigate statistical entropy of a 3-dimensional rotating acoustic black hole based on generalized uncertainty principle. In our results we obtain an area entropy and a correction term associated with the noncommutative acoustic black hole when λ introduced in the generalized uncertainty principle takes a specific value. However, in this method, it is not needed to introduce the ultraviolet cut-off and divergences are eliminated. Moreover, the small mass approximation is not necessary in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…The entropy can be interpreted as from the property of the horizon, but it can also be interpreted with other ways, i.e. brick wall model [22][23][24][25] that assumes the black hole is under an equilibrium state with the thermal gas surrounding it.…”
Section: Thermodynamic Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The entropy can be interpreted as from the property of the horizon, but it can also be interpreted with other ways, i.e. brick wall model [22][23][24][25] that assumes the black hole is under an equilibrium state with the thermal gas surrounding it.…”
Section: Thermodynamic Identificationmentioning
confidence: 99%
“…Next, as for thermodynamics of a gravitational black hole, the description has usually to be made with the help of proper expressions for the mass and the entropy of the acoustic black hole. Some recent developments had showed that the entropy could be endowed to an acoustic black hole by understanding the microscopical modes in some situations [22][23][24][25]. But the mass is definitely relevant to the classical dynamics, and thus its definition requires an analogue for gravity's equation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several works have been devoted to investigating the effect of GUP on computing the Hawking radiation from black holes in 2 + 1 dimensions. In this sense, the Hamilton-Jacobi method via the WKB approach to calculate the imaginary part of the action is an effective way of investigating the Hawking radiation as a process of tunneling particles from a black hole [24][25][26][27][28][29][30]. In [31], the effect of GUP on the Hawking radiation from the BTZ black hole has been investigated using the modified Dirac equation.…”
Section: Introductionmentioning
confidence: 99%
“…We can also mention the self-dual black hole [39,40], which is another example of a quantum-corrected black hole. In [41], by extending the thermodynamic analyzes performed in [42], the Hawking radiation from a self-dual black hole with GUP was investigated via tunneling formalism [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%